Biological studies on the natural enemies in suppression of coconut stick insect, Graeffea crouanii (Le Guillou) in Fiji - Deesh, Aradhana; Joshi, Ravindra; Jokhan, Anjeela; Khan, Mohammed; Jerard Bosco, Augustine (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2020)
Coconut stick insect, Graeffea crouanii (Le Guillou) is one of the important pests of coconut palms in Fiji. It causes extensive leaf damage resulting in production losses. The field surveys revealed the presence of several naturally-occurring natural enemies (predators and parasitoids) on G. crouanii in the major coconut growing regions in the Fiji Islands viz., Viti Levu, Vanua Levu and Taveuni. Two species of egg parasitoids, Paranastatus verticalis Eady and Paranastatus nigriscutellatus Eady were recorded as the most prevalent natural enemies, of which P. verticalis was the dominant species. This paper presents information from field and laboratory studies on the pest and dominant natural enemy and role of P. verticalis on the population suppression of G. crouanii in Fiji. The release of P. verticalis and field sanitation were the two best management practices identified that contributed to the improvement of plant health toward the management of G. crouanii.